Mycobacterium tuberculosis H(37)Ra ESAS-7—An excretory-secretory antigen fraction of immunodiagnostic potential in pulmonary tuberculosis - Nair, E. Raji (Springer India, 1998)
A mycobacterial excretory-secretory protein fraction ESAS-7 purified by 50% ammonium sulphate precipitation followed by SDS-PAGE fractionation was evaluated by penicillinase enzyme linked immuno-sorbent assay (ELISA) for its sensitivity and specificity in the diagnosis of pulmonary tuberculosis. At a “cut off” serum dilution of 600, 38 (90%) of 42 sera from bacteriologically confirmed tuberculosis cases, 15 (100%) of 15 sera from bacteriogically negative but anti tubercular therapy (ATT) responded cases, 3 (7%) of 43 sera from normal healthy subjects and 4 (8%) of 48 sera from non tuberculous disease control cases gave positive reaction for tubercular antibody to ESAS-7 antigen fraction containing predominantly 33-kDa protein with a sensitivity of 90% in bacteriologically confirmed cases and specificity of 92%. Further, this diagnostic assay using the ESAS-7 antigen is more sensitive requiring as little as one nanogram antigen per test compared to use of 100 nanogram EST-6 antigen reported earlier. Thus use of ESAS-7 antigen for antibody detection has good diagnostic potential with improved specificity in pulmonary tuberculosis.